Analysis of Factors Influencing Economic Growth in Central JavaProvince in 2017-2021 - Nirmala Sena Dipayani; Nur Hidayah (www.amertainstitute.com, 2023)
This study aims to analyze the effect of the regional minimum wage (UMR), human development index (IPM), labor force participation rate (TPAK) and poverty on economic growth in districts/cities in Central Java Province during the period 2017 - 2021.The analytical tool used in this study, namely panel data regression. The data used in this study are time series and cross section data obtained from the Central Bureau of Statistics(BPS) of Central Java. The model chosen in this study is REM. Based on the results of theanalysis, it is known that the UMR has a positive and significant relationship, HDI has a positive and significant relationship, while TPAK has a negative and not significant relationship, meanwhile, poverty has a negative and significant relationship. Based on theresearch that has been done, the government can increase the UMR and liveability as wellas guarantee public education to increase economic growth